Lateral caudal axial pattern flap in 13 dogs. Issue 5 (10th June 2015) - Montinaro, Vincenzo; Massari, Federico; Vezzoni, Luca; Liptak, Julius M.; Straw, Rod C.; Allen, Larie; Cavanaugh, Ryan P.; Berg, John; Doyle, Ronan S.; Buracco, Paolo; Romanelli, Giorgio
<x xml:space="preserve">Abstract</x> Objective To describe the frequency and extent of complications associated with lateral caudal axial pattern flaps used to cover large traumatic or excision skin defects on the dorsum, gluteal, and perineal region in 13 dogs. Study Design Case series. Animals Thirteen client‐owned dogs. Methods Medical records from 8 institutions were reviewed for dogs treated with a lateral caudal axial pattern flap, including cases in which the procedure was combined with other reconstructive techniques. The flap length relative to the tail length, location of tail skin incision, size and cause of the defect, and short‐ and long‐term complications were recorded. Results Thirteen dogs were included, 11 with tumors and 2 with traumatic skin loss. The mean estimated length of the flap relative to tail length was 51% (range 33–70%). Four dogs had wound complications. This included 2 dogs with minor postoperative wound complications (mild distal dehiscence) that did not require surgical revision and 2 dogs with major complications that required surgical revision. Two of these 4 dogs had distal flap necrosis, one was revised surgically and one was managed conservatively. In these 2 dogs, the flap length was estimated as 80% and 65% of the tail length, respectively. At 30 days, flaps in all dogs were completely healed. No long‐term complications were recorded in any dog. For some dogs, the reconstruction was not obvious, with only the change in hair direction and color noticeable. Conclusion Lateral caudal axial pattern flap is a reconstructive option for gluteal, dorsal, and perineal skin defects in dogs. Distal flap necrosis and dehiscence due to wound infection occurred in 4 dogs that required additional wound care but not always surgical revision.